MiR-128-3p directly targets VEGFC/VEGFR3 to modulate the proliferation of lymphatic endothelial cells through Ca2+ signaling. (September 2018) - Zhou, Jie; He, Zhiyou; Guo, Le; Zeng, Jizhang; Liang, Pengfei; Ren, Licheng; Zhang, Minghua; Zhang, Pihong; Huang, Xiaoyuan
Highlights: VEGFC/VEGFR3 affects LECs proliferation and Ca 2+ release. VEGFC and VEGFR3 are direct downstream targets of miR-128. MiR-128 modulates LEC proliferation and Ca 2+ release in LECs. Abstract: Lymphangiogenesis has been regarded as a physiological response to pathologic stimuli. The abnormal proliferation of lymphatic endothelial cell (LECs) and lymphangiogenesis is involved in the development of lymphatic disorders. Reportedly, VEGFC/VEGFR3 plays a key role in lymphangiogenesis; moreover, VEGFC/VEGFR3 exerts their cellular effects through activation of Ca 2+ signaling in several cell types. Herein, we demonstrated that VEGFC significantly up-regulated LEC proliferation through VEGFR3; moreover, VEGFC/VEGFR3 induced Ca 2+ signaling activation. By using online tools, miR-128 and miR-3916 were predicted as candidate upstream miRNAs which might target VEGFC/VEGFR3. As verified using Immunoblotting assays, miR-128 significantly regulated the protein levels of VEGFC/VEGFR3, whereas miR-3916 only slightly modulated VEGFC and VEGFR3 proteins. Contrary to VEGFC, miR-128 overexpression remarkably suppressed LEC proliferation, Ca 2+ release and ERK1/2-Akt signaling; moreover, the effect of VEGFC could be partially attenuated by miR-128. In summary, miR-128 interacts with the 3′-UTR of VEGFC and VEGFR3 to inhibit their expression, thus suppressing LEC proliferation through Ca 2+ and ERK1/2-Akt signaling. Taken together, we provided novel experimental basis for miRNA-regulated LEC proliferation through Ca 2+ signaling.